Sustainable Transformation of Agrifood Systems: A Circular Economic and Agroecological Perspective - Acharya, Ganga Dutta (SAARC Journal of Agriculture, 2023)
Agri-food systems have increasingly faced complex socio-economic and biophysical challenges. Poverty, inequalities, low productivity, food insecurity, resources degradation, loss of biodiversity, and climate change are some of the pertinent challenges demanding immediate attention. There is an increasing realization that current dominant model of development characterized by excessive use of resources, constantly poses negative externalities to the environmental health, climate and human welfare. Since agricultural development policies and practices are key to addressing these issues, there have been compelling calls for adequate policy environments for the profound transformation of agri-food systems to achieve better nutritional, environmental, and sustainability outcomes. Circular economy and agroecological approaches are widely recognized as providing credible pathways to develop inclusive, sustainable and resilient agri-food systems. While there is plethora of studies on agroecology and circular economy in international arena but studies on potential application and implications of these measures in Nepalese context remain unexplored. Furthermore, the circular economic framework is mainly used in industries and yet to be adapted in the agriculture sector. Based on systematic reviews and analysis of academic literatures we propose a framework for sustainable transformation of agrifood systems that encompasses both the circular economic and agroecological principles. We argue that the framework offers plausible solutions to the pressing need of reducing negative externalities of agri-food systems. However, agricultural research, education and development systems are traditionally entrenched by reductionist traditions that poorly accommodate the complex epistemological issues of circular economy and agroecology, and hence are the potential barriers for effective application in Nepalese context. SAARC J. Agric., 21(1): 1-12 (2023)